The Effectiveness of PowerPoint-Assisted Classical Guidance Services in Enhancing Students’ Learning Motivation - Pikri Nopen (CERDAS AKADEMIKA NUSANTARA, 2025)
Learning Learning motivation is one of the important factors that determine students' success in achieving academic achievement. However, in practice, there are still many students who show low levels of learning motivation, so appropriate intervention efforts are needed to increase their enthusiasm and involvement in the learning process at school. This study aims to describe the level of learning motivation among Grade XI students at SMA Negeri 4 Kota Bengkulu and to test the effectiveness of classical guidance services assisted by PowerPoint media in increasing it. The approach used is quantitative with a quasi-experimental method through a one-group pretest-posttest design, allowing for a comparison of students' conditions before and after the treatment. The research subjects consisted of 29 students in class XI IPS 3 who were selected randomly using random sampling techniques. A validated Likert scale questionnaire was used to measure learning motivation, while data analysis was performed using a paired sample t-test. The results showed a significant increase in learning motivation after students participated in classical guidance services assisted by PowerPoint media. Thus, the treatment provided proved to be effective in increasing student learning motivation.